Pengaruh Ukuran Perusahaan, Profitabilitas, Cash Holding, Debt To Equity Ratio Dan Net Profit Margin Terhadap Perataan Laba - Siti Dewi Kusmiyati; Mohamad Zulman Hakim (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2020)
The purpose of this study was to determine the effect of company size, profitability, cash holding, debt to equity ratio and net profit margin (NPM) on income smoothing. The population in this study includes all manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. The sampling technique uses purposive sampling method. Based on established criteria, 19 companies were obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange (IDX) website. The analytical method used is logistic regression analysis. The results showed that partially, the size of the company that was proxied by size had a significant negative effect on income smoothing, profitability which was proxied by return on assets (ROA) and net profit margin did not have a negative effect on income smoothing, cash holding had a significant positive effect on income smoothing, While the debt to equity ratio does not have a positive effect on income smoothing.